Analysis of Recognition and Protection of Indigenous Peoples Rights in Land Policy in Indonesia - Dedy Muharman (Journal of Adat Recht, 2025)
This study aims to examine the recognition of Indigenous land rights in Indonesia, the challenges faced in their implementation, and provide policy recommendations to strengthen the protection of Indigenous rights in the land sector. Although Indonesia already has regulations that recognize indigenous peoples ' rights, such as the 1945 Constitution and various sectoral laws, implementation of recognition of Indigenous land rights is often hampered by regulatory overlap and conflicts of interest between the forestry, plantation, and mining sectors. In addition, the role of indigenous peoples in policy making is still limited. This study identifies the gap between regulation and field reality, as well as analyzing the social, economic, and environmental implications of the recognition of Indigenous land rights. The results showed the importance of harmonizing regulations, increasing the participation of indigenous peoples, and accelerating the certification of indigenous lands to increase legal certainty. This study suggests multi-stakeholder collaboration as a strategic step to strengthen the position of indigenous peoples in the management of their lands and Natural Resources.